2022
DOI: 10.3390/jintelligence10010007
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility to Change the Solution: An Indicator of Problem Solving That Predicted 9th Grade Students’ Academic Achievement during Distance Learning, in Parallel to Reasoning Abilities and Parental Education

Abstract: The relation between academic achievement and various measurements of cognitive abilities, problem-solving skills and self-managed learning has been established in the research before the COVID-19 pandemic and distance learning. The aim of the current research was to analyze the extent to which these aspects predicted the educational achievement of 9th grade students (mean age 15.4 years) during distance learning, when students had to do relatively more tasks independently, organize their daily learning and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…However, it was interesting that students' selfreported level for available technical means to carry out distance learning was not significantly different, similarly to the results self-assessment measurements of self-management and problem-solving skills. Altogether, the current results confirm previously established role that cognitive abilities play regarding academic achievement (e. g., Hacatrjana, 2022;Kampa et al, 2021). Not tackling the challenges some students have with learning early enough may lead to even larger discrepancies and the students might find it harder to grasp increasingly complex curriculum, leading to risks of dropping out of school.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, it was interesting that students' selfreported level for available technical means to carry out distance learning was not significantly different, similarly to the results self-assessment measurements of self-management and problem-solving skills. Altogether, the current results confirm previously established role that cognitive abilities play regarding academic achievement (e. g., Hacatrjana, 2022;Kampa et al, 2021). Not tackling the challenges some students have with learning early enough may lead to even larger discrepancies and the students might find it harder to grasp increasingly complex curriculum, leading to risks of dropping out of school.…”
Section: Discussionsupporting
confidence: 88%
“…Research on educational and psychological aspects during the pandemic has been focused on various aspects, such as students' individual attitudes, well-being and academic outcomes (e. g., Hacatrjana, 2022;Scott et al, 2021), as well as risks of not returning to schools after the pandemic (UNESCO, 2020), and these results indicate that there were variations in how students and education systems (Barron Rodriguez et al, 2021;Lindblad et al, 2021;Morgan, 2022) dealt with distance learning. For some students it was easier to deal with distance learning than for others (Hacatrjana, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that these variables would be also crucial for students to keep their academic performance during the pandemic. Indeed, it was shown that results of tests in Mathematics and in the native language (Latvian) at the end of primary school (9th grade) during the pandemic were related to reasoning abilities, selfassessed problem-solving skills, self-management skills, and parental education level (Hacatrjana, 2022). Similar results would be expected from the analysis of the academic achievement of 11th grade students.…”
Section: Relation Between Academic Achievement and Other Variablessupporting
confidence: 54%
“…In a study with high-school students it was discovered that students' self-directed learning skills, especially skills for using digital learning tools and planning skills, were sufficient during the distance learning, based on their own evaluations, though they admit to having problems with assessing their learning gaps (Lāma, 2021). Data from the pandemic period show that self-management skills were correlated to students' test results in math and language but were not statistically significant predictors of these results, compared to other variables (Hacatrjana, 2022).…”
Section: Relation Between Academic Achievement and Other Variablesmentioning
confidence: 99%
See 1 more Smart Citation